PENILAIAN TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE CAMEL STUDI KASUS PADA PT. BANK PEMBANGUNAN DAERAH JAWA TENGAHTAHUN 2009 â 2014 - Didik Riadi Baptista, 12.05.62.0011 (Students Journal of Economic and Management, 2015)
Banking is the backbone in building Indonesias financial system and the economy because it can serve as an intermediary institution is an institution that is able to channel back funds owned by units of the economic surplus economic units that require funding or deficit. Therefore, in order to run smoothly then banking institutions should run well too. Every company, both banks and non-banks at a time (given period) will report all financial activities. This financial report aims to provide financial information, either to the owner, management, as well as interested outside parties against the report. The purpose of the establishment of the bank is to manage the finances of the region, namely as the holder of Treasury and help boost the local economy by providing credit to small entrepreneurs. Central Java Regional Development Bank is a bank-owned Central Java Provincial Government together with the City / County Central Sejawa. The research objective of this study aimed to analyze the soundness of PT. Central Java Regional Development Bank using the CAMEL ratios include the capital, assets, management, earnings and liquidity. Based on the results of the calculation of the net value of each ratio shown in the table above shows the sum of the net worth of all aspects (CAMEL) in 2009 amounted to 102.1% in 2010 amounted to 95.81%, out 2011 at 89.66%, in 2012 sbesar 91.56%, in 2013 amounted to 94.08% and in 2014 amounted to 93.26%. Based on the assessment criteria for the assessment aspects of CAMEL Central Java Regional Development Bank of the year 2009 - 2014 is HEALTHY. Keyword : Captal, Asset, Management, Earning, Liquidity